2018
DOI: 10.1177/1076217517750701
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Education in Ireland

Abstract: This article provides an overview of recent developments in gifted education in Ireland. It highlights changes in attitudes, educational policies, gifted education programs, and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In New South Wales, Australia, a review of selective schools for gifted and talented students in the state found that unintended barriers may deter some gifted students, and notably Aboriginal students, students with special education needs, and rural and remote students, from sitting selective tests (NSW Department of Education, 2018 [57]). The review also highlighted the shortcomings of the test design of school assessment processes in acting as a further barrier in the identification of the aforementioned groups.…”
Section: Considering the Effect Of Definition On The Identification O...mentioning
confidence: 99%
See 2 more Smart Citations
“…In New South Wales, Australia, a review of selective schools for gifted and talented students in the state found that unintended barriers may deter some gifted students, and notably Aboriginal students, students with special education needs, and rural and remote students, from sitting selective tests (NSW Department of Education, 2018 [57]). The review also highlighted the shortcomings of the test design of school assessment processes in acting as a further barrier in the identification of the aforementioned groups.…”
Section: Considering the Effect Of Definition On The Identification O...mentioning
confidence: 99%
“…Advocates for the use of specific provisions such as selective schools maintain that these might provide social and emotional benefits for gifted students and help them reach their full potential, which will ultimately benefit society. Importantly, they can provide students with the opportunity to learn alongside like-minded peers in a supportive environment that accepts and celebrates their high ability and talents (NSW Department of Education, 2018 [57]; Eyre, 2012 [122]).…”
Section: Educational Offer and Learning Settings: Between Egalitarian...mentioning
confidence: 99%
See 1 more Smart Citation